ESCISIÓN Y TRAGEDIA DEL HÉROE ROMÁNTICO EN LES DEUX MAÎTRESSES DE ALFRED DE MUSSET - Ramos Gay, Ignacio (Anales de Filología Francesa, 2006)
The tragic split of the romantic hero is a constant feature within Alfred de Musset’s work which tends to be represented by the image of the double. This essay explores its presence in Musset’s short story Les deux maîtresses, and its transposition in the two antagonistic women who are the object of his love. The main character’s tragedy will derive from his perennial attempts to reconcile both contraries and from the consequent frustration resulting from his awareness of the impossibility to adapt his will to reality.